FLORISTIC CONDITIONS IN THE STEPPIC ZONE - Madami Djamila; Hiouani Fatima; Tarai Nacer; Abdou Yamina (Natural Resources and Sustainable Development)
The Steppic zones are strong milieus with low and irregular rainfall, and Steppic vegetation and soil. However, there are always conditions that are favorable for the existence of a spontaneous flora in the edapho-climatic and anthropic stresses. This study aims at making a preliminary evaluation of the floristic conditions (biological types and floristic wealth) in the Steppic zone of the region of M’cif. The sampling was carried out using the minimal area method that requires collecting all the vegetal species in a limited surface. The sampling shows only steppic species that adapt to the milieu. It includes edaphic ecological groups that embody the action of the edaphic actors on the floristic, psammophile, and halophile composition of the vegetal communities. Among the most remarkable species in this zone, we find Retama retam, Atriplex halimus, and Salsola vermiculata. This vegetation is a witness of the belonging to an anthropized zone (agro-pastoral zone).